Who collaborates with the Soviets? Financial distress and technology transfer during the Great Depression - Jerry Jiang; Jacob P. Weber (Federal Reserve Bank of New York, 2024)
We provide evidence that financial distress induces firms to sell their technology to foreign competitors. To do so, we construct a novel, spatial panel dataset by individually researching and locating U.S. firms who signed Technology Transfer Agreements (TTAs) with the Soviet Union during the 1920s and 1930s in various U.S. counties. By relating the number of TTAs signed in each county to the number of bank failures, we establish a significant, positive relationship between financial distress and the number of firms signing TTAs with the Soviet Union. Our findings suggest that banking panics may create opportunities for foreign countries to acquire affected firms' technology.
Keywords: G21; N6; O33; 330; banking panic; technology assistance; know-how diffusion; industrialization; industrial policy